Flexible and Sustainable Incremental Houses: Advancing Semi-Volumetric Systems of Prefabricated Construction for Rapid Urbanization in Indonesia - Viata Viriezky; Dalhar Susanto; Miktha Farid Alkadri (Infrastructures)
The Indonesian population is projected to increase by 66.65 in 2035 due to the continuous rise in urbanization globally. The growth contributed to the growing housing backlog and limited availability of residential spaces. This led to the evolution of incremental housing construction as an appropriate solution to residents’ needs. However, several factors hinder the implementation of incremental housing, including prolonged construction durations that delay the completion of an entire house, compromised quality of workmanship and materials, as well as poor flexibility. Conventional on-site construction, with concrete serving as the main material, led to prolonged construction time, difficult renovation, and untreatable waste. Preliminary studies have been conducted on incremental housing from urban development and financial perspectives, with none on alternative construction systems. Therefore, this study aimed to develop flexible and sustainable incremental housing with an assembly–disassembly system capable of reducing construction time and waste. This study experimented on the connection systems through digital simulations and prototypes leading to a construction system that combines frames and panels in a semi-volumetric system. It also combined a plug-and-play connection type to achieve the highest assembly–disassembly efficiency value (0.07), the lowest waste (below 25%), and a 30% shorter construction time. The result showed no displacement when tested with a load of up to 3 tons. This study contributed to the growing body of knowledge on alternative incremental house construction techniques, paving the way for more adaptable and environmentally responsible housing solutions in urban settings, particularly in rapidly urbanizing regions like Indonesia.